2013
DOI: 10.1177/0269094213496610
|View full text |Cite
|
Sign up to set email alerts
|

Where next for neighbourhood regeneration in England? Two years on

Abstract: This article updates previous research published in Local Economy in 2011 that examined the changing context of neighbourhood regeneration policy and practice in the first year of the UK Conservative-Liberal Democrat Coalition Government. At that juncture, based on early signs of political and policy direction, we set out what the policy and practice landscape might 'look like' for neighbourhood regeneration organisations over the next few years, given that the emerging policy framework appeared barren. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Through observing actual regeneration practice over the long-term, the case study findings have helped to develop a more nuanced understanding of the roles of external organisations within small town regeneration. Viewing the UCV experiment through the more contemporary lens of austerity, with the implied greater pressure to prioritise the use of funding, externally prescribed processes of change, such as the UCV renaissance, are less likely to occur (Deas and Doyle, 2013;Broughton et al, 2013). Whilst there are good reasons to be concerned about the lack of government regeneration funding, it is important to reflect on the fundamental challenges of such approaches identified within this paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through observing actual regeneration practice over the long-term, the case study findings have helped to develop a more nuanced understanding of the roles of external organisations within small town regeneration. Viewing the UCV experiment through the more contemporary lens of austerity, with the implied greater pressure to prioritise the use of funding, externally prescribed processes of change, such as the UCV renaissance, are less likely to occur (Deas and Doyle, 2013;Broughton et al, 2013). Whilst there are good reasons to be concerned about the lack of government regeneration funding, it is important to reflect on the fundamental challenges of such approaches identified within this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, local collaboration around a shared strategy may be important in helping to provide a 'greater sense of purpose and direction' and for local actors to 'know what grants to go for, rather than being driven by random funding opportunities' (Daniels et al, 2007, pxxii;Luther and Flora, 2000, p8). In the context of austerity and with less funding available, local contestation between individual towns may increase (Broughton et al, 2013), but such competition within an area can be wasteful, with 'each [town] seeking to attract the interest of developers, investors and occupiers' rather than working together to address common challenges (Healey, 1995, p225;Markey et al, 2012;Bentley and Pugalis, 2013).…”
Section: Collaboration To Enhance Local Agencymentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in funding streams could potentially stymie expertise from external and inventive approaches that seek to leverage and create resources for local communities to sustain them through the austerity period. Yet, as this case study demonstrates, opportunities to regenerate City-Regions and their communities through an engagement with culture is not impossible, but actually present a viable and successful way of navigating and negotiating 'the policy landscape they now face' [23]. As such, this paper concludes with a call for a more longitudinal analysis of the impact of community art and creative writing workshops on making lasting impacts on communities, and more funding opportunities for such work to be undertaken.…”
Section: Learning and Legaciesmentioning
confidence: 93%
“…Following policy shift, the empirical research identified that the organisational factors prior to policy Empirical evidence across the relevant case study organisations suggested a significant weakening of a sense of community 'ownership' of the NR process (Factor 1). Neighbourhood-based policy instruments and funding streams from the previous Labour government were abolished by the new Coalition Government, replaced by 'Big Society' and 'Localism' self-help initiatives with minimal funding that lend themselves to wealthier communities with resources of their own (Broughton et al, 2013b). Second, evidence suggested that 'brokerage' had narrowed its focus on income generating activities with primarily economic goals (Factor 2).…”
Section: Organisational Factors Critical To Sustainable Nr Practice A...mentioning
confidence: 99%